Case Report: Migraine-Induced Dystonia of the Lower Extremities - Jiang, Ting; Xie, Yinyin; Maimaiti, Buajieerguli; Cheng, Yu; Li, Zhaoran; Meng, Hongmei (Frontiers in Neurology, 2022)
Migraine is a highly prevalent neurological disorder characterized by recurrent, unilateral, or bilateral throbbing severe headaches. Currently, there are extremely rare cases of migraine-induced dystonia. A 52-year-old woman was admitted for intractable migraine for about 5 days and walking difficulties for 1 day. The symptom of an inability to walk appeared on the fourth day of the headache attack lasting for 1 day and resolved on its own as the headache subsided. The same symptoms appeared once 6 years ago. Neurological examination, brain Magnetic resonance imaging (MRI), laboratory tests of blood and cerebrospinal fluid (CSF) were normal. The contrast transcranial Doppler echocardiography (cTCD) revealed a latent and massive right-to-left shunt (RLS) after the release of the Valsalva maneuver. The patient was diagnosed with migraine-induced dystonia of the lower limbs. Oral ibuprofen and flunarizine and avoidance of increased chest pressure maneuvers were used for treatment and prevention. During the 6-month follow-up, the patient was free of headaches and walking difficulties. Our study reported a rare case of migraine-induced dystonia of the lower extremities.